Esquemas de comunicação cooperativa segura considerando regimes parciais de segurança, múltiplas antenas e blocos de tamanho finito - Farhat, Jamil de Araujo (2018)
The growing demand for wireless communications systems makes security an important and difficult design task. Therefore, in this thesis we approached different studies at physical layer security considering different scenarios of partial secrecy requirements, multiple antennas and finite blocklenghts. With respect to the partial secrecy regime, we evaluate the secure energy efficiency (SEE) of a cooperative network subject to partial secrecy requirements, implemented through a fractional equivocation parameter θ ϵ (0, 1] that allows partial secrecy when θ < 1. We assume that only the channel state information (CSI) of the legitimate channel is available, while the CSI with respect to the eavesdropper is unknown. Then, we propose a CSI-Aided Decode-and-Forward (DF) scheme, in which the transmitter uses the available CSI in order to choose between direct and cooperative paths. Moreover, the relay employs either Repetition Coding (CSI-RC), i.e., source and relay use the same codebook, or Parallel Coding (CSI-PC), when different codebooks are used. By resorting to the Dinkelbach algorithm, we propose a joint power allocation scheme, which also optimizes θ to maximize the SEE. Our schemes are compared with the traditional DF, Amplify-and-Forward (AF), and Cooperative Jamming (CJ). Extending the previous analysis, we also study the SEE in a cooperative scenario where all nodes are equipped with multiple antennas. Moreover, we employ secrecy rate and power allocation at Alice and at the relay in order to maximize the SEE, subjected to a constraint in terms of a minimal required secrecy outage probability. Considering this MIMO scenario in which only the CSI with respect to the legitimate nodes is available at Alice, we compare the Artificial-Noise (AN) scheme with CSI-Aided Decode-and-Forward (CSI-DF). Lastly, considering a more restrictive scenario with respect to the CSI, but more realistic, in which the legitimate transmitter has no knowledge of the instantaneous channel state information with respect to neither the legitimate receiver nor the eavesdropper, we investigate the secure throughput in a delay-critical scenario, such as in some applications of machine-to-machine communications, so that users communicate with a finite blocklength. In this approach, the performance of direct and selective decode-and-forward cooperative communication strategies are compared.